American Poet Jorie Graham: Hero of Both the Mind and Spirit (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2024)
“American Poet Jorie Graham: Hero of Both the Mind and Spirit” is an investigation of Jorie Graham’s thematic use of time as a manner of enhancing the artistic value of her work. Graham explores time’s dual nature as being both momentary and infinite—both belonging to the objective universe and to the particular individual. Through time, Graham reveals the secrets that us humans prefer to leave untouched.For additional context, listen to the author's reflection on the piece below.